Mitochondrial genome aberrations in skeletal muscle of patients with motor neuron disease. Issue 4 (1st May 2013) - Artuso, Lucia; Zoccolella, Stefano; Favia, Paola; Amati, Angela; Capozzo, Rosa; Logroscino, Giancarlo; Serlenga, Luigi; Simone, Isabella; Gasparre, Giuseppe; Petruzzella, Vittoria
Abstract: Our objective was to assess the role of defects of mitochondrial function as contributing factors in the pathogenesis and/or progression of amyotrophic lateral sclerosis (ALS); mitochondrial genome structural alterations were investigated. DNA lesions, point alterations and gross rearrangements were screened by specific applications of real-time PCR including an optimized rapid gene-specific method for the accurate quantification of mitochondrial DNA (mtDNA) lesions as well as sequencing on skeletal muscle biopsies of three patients presenting with motor neuron disease. We found a higher frequency of mtDNA lesions, including multiple deletions, particularly in the only SOD1 mutated patient as well as in a patient negative for mutations in SOD1 but presenting a severe form of the disease. The occurrence and the extent of mtDNA lesions of the cases here presented were consistent in all the examined clinical phenotypes of ALS (SOD1 related ALS, bulbar onset, spinal onset) and correlated with the severity of clinical course of the illness and with the presence of SOD1 mutation as well. In conclusion, the strong association with mtDNA damages supports the hypothesis that mitochondrial dysfunction in skeletal muscle may contribute to the pathogenesis and progression of ALS.